Unveiling the Impact of Brand Popularity on Consumer Satisfaction and Loyalty Among Halal Cosmetic Users - Buchori Muslim; M. Sulaeman Jajuli (LP2M IAIN Palopo, 2026)
This study investigates the interplay between brand popularity, consumer satisfaction, and brand loyalty, focusing on Halal Cosmetics Users in Indonesia. As consumer preferences increasingly align with brands that resonate with their personal values, understanding the mechanisms driving brand popularity and loyalty becomes crucial. The research examines how brand popularity influences consumer satisfaction and, subsequently, brand loyalty. Utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) for data analysis, the study finds that brand popularity significantly impacts both consumer satisfaction and brand loyalty, with consumer satisfaction serving as a critical mediator. These findings highlight the importance of effective brand positioning, strategic marketing, and maintaining high standards to foster strong consumer loyalty. The insights gained offer valuable implications for marketing strategies and brand management in the competitive halal cosmetics industry